THE MATHEMATICS CONCEPTS IN PHYSICS TRAINING IN SECONDARY SCHOOLS - Dehqonova, Ohista; Qurbonov, Mirzaahmat; Taylanov, Nizom (Физико-технологического образование, 2022)
In the article we use the concepts of mathematics in conducting and analyzing physics classes in secondary schools. In order to ensure the continuity of physics and mathematics, we must pay attention to the sequence of topics in these textbooks. The following analyzes the relevance of topics in physics and mathematics in secondary schools